Law Enforcement Procedures for Police Members Involved in Drugs Abuse in the Polda Bengkulu - Panji Putra Pratama; Ismail Jalili (Journal of Sharia and Legal Science, 2023)
The aims of this study are: To analyze law enforcement procedures for members of the police who are involved in drug abuse. As well as a review of fiqh siyasa on law enforcement procedures for members of the police who are involved in drug abuse. This study is based on the fact that there are still members of the police who commit criminal acts of drug abuse. This type of research is qualitative-empirical research by examining documentation and interviewing informants. This study concludes that: (1) Law Enforcement Procedures for members of the Police in enforcing the law against members of the Police who commit or abuse drugs in the field of service, enforcement of discipline, order and internal security have been going well, the implementation of law enforcement has been carried out but not yet optimal, marked by the fact that there is still drug abuse by police officers, while efforts to prevent drug abuse by members of the police are carried out by carrying out activities related to religion, increasing supervision in terms of the discipline of members of the police, and applying strict sanctions against persons who abuse drugs. (2) In the review of fiqh siyasa syar'iyah, the efforts of the police in taking action against members who are involved in drug abuse are in accordance with Islamic values, namely imposing disciplinary punishment and trial on the police code of ethics, which aims to bring benefits to members of the police, the National Police institution and society and prevent harm that will occur.